Eco-Friendly Synthesis of Zinc Oxide: Green Chemistry Approaches and Innovations - Kamal, Ayaa; H. Alwash, Atheel; Al-Sarraj, Emad; Gholami, Fatemeh; Thiab, Noor (Al-Nahrain Journal of Science, 2025)
Techniques of green production of zinc oxide nanoparticles, also called ZnO-NPs utilizing extracts of plants have drawn study interest in sustainable innovation due to its low cost, ease of use, and benefits for the natural world. This review presents a sustainable method for synthesizing zinc oxide nanoparticles, also known as ZnO-NP from plant extracts, and the features of zinc oxide nanoparticles are examined. These physical features attest to zinc oxide form, structure, crystal formation, and proportions. The dimensions form and dimensions significantly influence the zinc oxide nanoparticle's interface reactivity. A further benefit of capping compounds as stabilizing agents that limit nanoparticle growth, and avert the accumulation and disintegration in colloid synthesizing, is presented in the article review. The capping ligands maintain the connection between nanoparticles and their formation medium. Ultimately, zinc oxide has become one of the most favored options for the use of sunlight because of its spectral properties. The mechanism and its application in different fields have been summarized.